2019
DOI: 10.1002/rth2.12206
|View full text |Cite
|
Sign up to set email alerts
|

Fully automated thromboelastograph TEG 6s to measure anticoagulant effects of direct oral anticoagulants in healthy male volunteers

Abstract: Background The ability to assess the hemostatic effect of the direct oral anticoagulant (DOACs) may be valuable in clinical situations such as bleeding or thrombosis, before urgent surgery, or reversal of anticoagulation. We sought to assess the anticoagulant effect of DOACs with the new‐generation fully automated thrombelastograph TEG 6s using resonance‐frequency viscoelasticity measurements and disposable multichannel microfluidic cartridges. Methods A single dose of oral dabigatran 150 mg, rivaroxaban 20 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 19 publications
5
69
0
Order By: Relevance
“…Studies have been performed with a developmental TEG 6s cartridge, where one channel with ecarin enables detection of dabigatran and another channel allows detection of FXa inhibitors. 18 , 30 TEG 6 s and ROTEM sigma each have 4 channels. With ClotPro, there are 6 channels and therefore a larger number of tests can be performed simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been performed with a developmental TEG 6s cartridge, where one channel with ecarin enables detection of dabigatran and another channel allows detection of FXa inhibitors. 18 , 30 TEG 6 s and ROTEM sigma each have 4 channels. With ClotPro, there are 6 channels and therefore a larger number of tests can be performed simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…But this study was limited in terms that the R-value was measured only 3-time points over 3 hours rather than more time points over 12 to 24 hours and only on nine healthy young males [40]. This study reflected that DOACs primarily affect the whole blood clotting time [40].…”
Section: Thromboelastography (Teg) Test and Rivaroxabanmentioning
confidence: 91%
“…Therefore, this can be potentially used in presurgical patients receiving DOAC, including situations prior to cardioconversion or radiofrequency ablation procedures [40]. But this study was limited in terms that the R-value was measured only 3-time points over 3 hours rather than more time points over 12 to 24 hours and only on nine healthy young males [40]. This study reflected that DOACs primarily affect the whole blood clotting time [40].…”
Section: Thromboelastography (Teg) Test and Rivaroxabanmentioning
confidence: 96%
See 1 more Smart Citation
“…179 Recently, the TEG 6s has been assessed for the monitoring of DOACs. 180 It was demonstrated that the R parameter was the most sensitive and correlated with the DOAC concentration when assessed via the specific cartridge for factor Xa or thrombin inhibitors. 180 The predictive value of this assay was reported to be very high (>98%), which is particularly important in emergency situations.…”
Section: Ongoing Researchmentioning
confidence: 99%